What are the predictors for recurrence of Crohn's disease after surgery?. Issue 14 (9th April 2021) - Ozgur, Ilker; Kulle, Cemil Burak; Buyuk, Melek; Ormeci, Asli; Akyuz, Filiz; Balik, Emre; Bulut, Turker; Keskin, Metin
Abstract : Abstract: Surgical resection is an unavoidable part of the current treatment options for Crohn's disease (CD), and more than half of patients develop recurrence. The aim of this study was to investigate the predictors for recurrence in the long-term follow-up of CD patients after surgery. Medical records of consecutive CD patients who were operated on between January 2003 and January 2015 were retrospectively analyzed. Data including demographic and clinical characteristics of the patients were recorded. Recurrence was evaluated based on the Crohn's Disease Activity Index or endoscopic findings. The majority of 112 patients were males (n = 64, 57.1%), and 61 (54.4%) of them were active smokers. The median follow-up was 113 (range: 61–197) months. Disease recurrence occurred in 16 (14.3%) patients at a median of 13.5 months. The endoscopic recurrence rate was 8% (n = 9) at 1 year, 12.5% (n = 14) at 5 years, and 13.4% (n = 15) at 10 years. One (0.9%) patient underwent colonoscopic balloon dilatation at 1 year, and 7 (6.3%) patients needed re-resection at a median of 36 months. The age of the patient at the time of diagnosis ( P = .033), penetrating disease behavior ( P = .011), intra-abdominal abscess ( P = 0.040) and, concomitant fistula and intra-abdominal abscess ( P = .017) were associated with disease recurrence. Our study results suggest that the patients' age at the time of diagnosis, penetrating disease, intra-abdominal abscess, and concomitant fistula and abscess are the risk factors for CD recurrence after surgery.